KUALITAS PELAYANAN PEMERINTAH DESA ONONAZARA KECAMATAN TUGALA OYO KABUPATEN NIAS UTARA (Paradigma Good Governance Dalam Pelayanan Publik) - Oliver Berkat Hulu; Frans Kurniawan Fuadi; Andi Muhammad Rizki (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Public services are provided in a variety of ways by government agencies to meet the needs of the general public and carry out their duties in accordance with applicable laws, yet there are a lot of instances where inadequate services are provided. In this case, the community complained about Ononazara Village government services. To prove this, research must be conducted using qualitative and quantitative methods; hence, the current study is a campuran study that combines both research methods. Data collected during the interviews conducted in Desa Ononazara were compiled by conducting a survey that was distributed via a Google form to residents of the community there. Results of the evaluation that was conducted were not good.